Measurement of the Sub-carinal Angle on the Normal Chest Radiograph of Adult at BPKIHS, Dharan, Nepal - Jha, RK; Gupta, M K; Pant, AR; Pandey, NK (Journal of BP Koirala Institute of Health Sciences, 2020)
Background: The sub-carinal angle is an angle formed between the main right bronchus and leftbronchus clearly seen in adequately exposed chest radiograph, normally at the level of 5th thoracicvertebrae. Objective: To measure sub-carinal angle in relationship to different age, sex and body mass index inthe adult. Methods: A cross-sectional study was carried out in the Department of Radio diagnosis and Imaging at BPKIHS, Dharan from 27th April to 6th August 2017. Sub-carinal angle was measured on the normal chest radiograph in 392 adult patients. The data were analyzed using SPSS Version 11.5 and descriptive statistics percentage, Mean, Standard Deviation were calculated. For inferential statistics, Independent ‘t’ test and Pearson’s correlation were applied. Results: The sub-carinal angle ranged from 39°- 81.1° with mean value 60.17°+7.81°. The mean subcarinalangle for the male was 59.17°+8.19° and for female was 60.62°+7.49°. The mean sub-carinalangle was wider in female than male in our study; however, the difference in sub-carinal angle between male and female was statistically not significant (p> 0.05). There was negative correlationbetween sub-carinal angle and age (r= -0.168, p <0.01). The sub-carinal angle was positivelycorrelated with BMI (r= 0.100, p< 0.05). Conclusion: In our study, the mean sub-carinal angle was 60.17° ± 7.81°. The mean sub-carinal angle difference between male and female was statistically non-significant. There was negative correlation of sub-carinal angle with age and positive correlation with BMI. The reference value obtained from this study will be helpful to diagnose abnormal sub-carinal angle due to various pathologies.